2001
DOI: 10.1118/1.1352578
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resolution measurements in quasimonochromatic x rays with mosaic crystals for mammography application

Abstract: A novel x-ray source for mammography application is being investigated. Quasimonochromatic x rays have been produced via Bragg diffraction with a W-anode x-ray tube and a graphite mosaic crystal array. The system provides 18 keV x rays with an energy resolution deltaE/E approximately equals 0.12. A thorough analysis of the spatial resolution of the system has been performed in order to understand and quantify the effect of the introduction of an active optical element such as a mosaic crystal in the x-ray path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…In the last decade, a compact source which generates quasi-monochromatic beams with a conventional x-ray tube and a mosaic crystal monochromator has been developed. 7,8 Subtraction imaging at the iodine K-edge has been tested in the last few years using this x-ray beam facility, together with silicon strip detectors with single-photon counting capability. The obtained results demonstrated an interesting image quality also for iodine concentrations reduced with respect to normal clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a compact source which generates quasi-monochromatic beams with a conventional x-ray tube and a mosaic crystal monochromator has been developed. 7,8 Subtraction imaging at the iodine K-edge has been tested in the last few years using this x-ray beam facility, together with silicon strip detectors with single-photon counting capability. The obtained results demonstrated an interesting image quality also for iodine concentrations reduced with respect to normal clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…As far as mammography is concerned, the photon flux provided by the compact x-ray source may prove to be adequate. Indeed, previous studies showed that, in the mammography energy range, improvements are within the achievable increase of intensity (Gambaccini et al 2001). Since at iodine K-edge energies the x-ray beam is more penetrating we only need to optimize the optical system for maximum reflectivity.…”
Section: Resultsmentioning
confidence: 99%
“…However, the transfer from the rather complex physical environment to clinical routine has not been given so far. The current approach, which is similar to the concept described in the literature [16], focuses on monochromatic X-ray beams obtained from conventional X-ray tubes. Since monochromacity and high reflectivity have to be optimized for the generation of monochromatic X-ray beams with acceptable intensity, monochromators with HOPG crystals can be used favorably [16,17].…”
Section: Discussionmentioning
confidence: 99%